Structural Optimization of the Retractable Dome for Four Meter Telescope (FMT). (7th February 2017) - Pan, Nian; Li, Yuxi; Fan, Yue; Ma, Wenli; Huang, Jinlong; Jiang, Ping; Kong, Sijie
Abstract: Dome seeing degrades the image quality of ground-based telescopes. To achieve dome seeing of the Four Meter Telescope (FMT) less than 0.5 arcsec, structural optimizations based on computational fluid dynamics (CFD) simulation were proposed. The results of the simulation showed that dome seeing of FMT was 0.42 arcsec, which was mainly caused by the slope angle of the dome when the slope angle was 15° and the wind speed was 10 m/s. Furthermore, the lower the air speed was, the less dome seeing would be. Wind tunnel tests (WT) with a 1:120 scaled model of the retractable dome and FMT indicated that the calculated deviations of the CFD simulation used in this paper were less than 20% and the same variations of the refractive index derived from the WT would be a convincing argument for the validity of the simulations. Thus, the optimization of the retractable dome was reliable and the method expressed in this paper provided a reference for the design of next generation of ground-based telescope dome.